Hypocalcaemic Tetany After Total Thyroidectomy - Biswas, Nripendra Nath; Chaudhury, Wazir Ahmed; Khan, Jahangir Alam; Biswas, Akhil Chandra; Arif, Khan Mohammad; Ghosh, Subrata; Akter, Selina (Faridpur Medical College Journal, 2016)
Hypocalcaemic tetany is one the commonest complication after total thyroidectomy. It may cause significant morbidity. Early detection and treatment have better out come. The main objective of the study is to find the incidence of hypcalcaemic tetany in post operative period after total thyroidectomy and average interval period of hypocalcaemia following surgery. This was an observational study conducted in the department of Otolaryngology & head-Neck Surgery Sylhet M.A.G. Osmani Medical College Hospital during 1st January 2006 to 31st December 2007. Pre-operative routine investigation, Thyroid Function test, Ultrasonography thyroid gland and cytological evaluation by FNAC were done in all patients. Ten patient developed hypocalcaemia after surgery. Among them only one suffered from permanent hypocalcaemia. Most of the patient developed symptoms about 48 hours after surgery. The Incidence and time interval of development of hypocalcaemic tetany after total thyroidectomy found in the series fully coincides with the results of other researchers globally. Faridpur Med. Coll. J. Jul 2015;10(2): 59-62